Enhancing the Stability and Photothermal Conversion Efficiency of ICG by Pillar[5]arene-Based Host-Guest Interaction - Ding, Yue; Wang, Chenwei; Lu, Bing; Yao, Yong (Frontiers in Chemistry, 2021)
Indocyanine green (ICG) is a classical near-infrared (NIR) photothermal reagent that can be employed in clinical medical detection. Under neutral conditions, ICG can adsorb NIR light effectively for photothermal (PTT) and photodynamic (PDT) therapy. However, ICG is easily degraded in weak acid environments, which seriously restricts its application. In this work, a cationic water-soluble pillar[5]arene (WP5) was selected as the stabilizing agent for ICG. Thanks to the host-guest interaction between WP5 and alkyl sulfonate, the stability and the photothermal conversion efficiency of ICG increased remarkably upon addition of WP5 as investigated by UV-vis spectrum and photothermal studies. Furthermore, an in vitro study showed higher efficiency of WP5&ICG in killing cancer cells in a shorter treatment time than the free ICG. Hence, it is hopeful that WP5 can be a new type of supramolecular host in enhancing the stability and photothermal conversion efficiency of photosensitizers.